2016
DOI: 10.1080/02701960.2015.1115979
|View full text |Cite
|
Sign up to set email alerts
|

Teaching dementia care to physical therapy doctoral students: A multimodal experiential learning approach

Abstract: As the population aged 65 and older grows, it becomes imperative for health care providers to expand their knowledge regarding geriatric conditions and concerns. Dementia is a devastating degenerative disease process that is affecting millions of individuals in the United States, with significant economic and emotional burden on family and caregivers. The need for further dementia education in physical therapy school is essential to improve attitudes and treatment that affect patient outcomes and quality of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 15 publications
2
38
0
Order By: Relevance
“…Our study demonstrated the positive finding that knowledge of dementia has improved among physiotherapists in the intervening years, likely reflecting an advancement in both research and clinical practice. Lorio et al (Lorio, Gore, Warthen, Housley, & Burgess, 2017) found increased knowledge and education among physiotherapy students resulted in positive attitudes towards working with people who have dementia. Education during the training of physiotherapists is essential, as our study demonstrated a minority of respondents reported having obtained additional education related to dementia outside of their physiotherapy degree.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the positive finding that knowledge of dementia has improved among physiotherapists in the intervening years, likely reflecting an advancement in both research and clinical practice. Lorio et al (Lorio, Gore, Warthen, Housley, & Burgess, 2017) found increased knowledge and education among physiotherapy students resulted in positive attitudes towards working with people who have dementia. Education during the training of physiotherapists is essential, as our study demonstrated a minority of respondents reported having obtained additional education related to dementia outside of their physiotherapy degree.…”
Section: Discussionmentioning
confidence: 99%
“…The students in the sample only received a single 2-hour lecture on physical therapy and the patient with dementia and only a little over half of the student felt that their training was adequate. The work by Lorio et al 20 demonstrated that a 12-hour multimodal training program for physiotherapy students yielded increased confidence and knowledge of working with people with dementia, this provides support for more comprehensive training in the curriculum prior to students going out on clinical placements.…”
Section: Discussionmentioning
confidence: 97%
“…19 Importantly, a structured intervention program to enhance doctoral physiotherapy students perceived sufficiency of knowledge and skill related to dementia resulted in greater confidence and predicted willingness to work with older adults. 20 An understanding of physiotherapy students' perceptions of working with people with dementia and the experiences that inform their attitudes, both outside and within their clinical training, has limited research. As the number of people with dementia increase, physiotherapy students will have direct contact with people with dementia across all clinical settings (e.g., acute care, rehabilitation hospital, and outpatient community settings) during training and will need to be able to work with this patient group upon graduation.…”
Section: Introductionmentioning
confidence: 99%
“…PWD experience barriers to receiving healthcare, resulting in fewer rehabilitation services, 5,7,8 and providers report feeling ill equipped to address the needs of this population with limited time and resources. 5,9 Further, rehabilitation studies typically exclude subjects with dementia diagnoses, rendering the effect of therapy services utilization for PWD unclear. 10 The physical activity and exercise interventions provided by PT slow functional decline, improve balance, and reduce fall risk in PWD [10][11][12] ; however, the efficacy of home health PT for physical function improvement in PWD is unknown.…”
mentioning
confidence: 99%
“…These impairments impact quality of life, reduce caregiver well‐being, and increase healthcare costs; however, the effect of physical therapy (PT) rehabilitation services on dementia‐associated decline is unclear. PWD experience barriers to receiving healthcare, resulting in fewer rehabilitation services, and providers report feeling ill equipped to address the needs of this population with limited time and resources . Further, rehabilitation studies typically exclude subjects with dementia diagnoses, rendering the effect of therapy services utilization for PWD unclear …”
mentioning
confidence: 99%